Mechanism of microbiologically influenced corrosion of X52 pipeline steel in a wet soil containing sulfate-reduced bacteria. (1st November 2017) - Liu, Hongwei; Frank Cheng, Y.
Highlights: Pipeline steel corrosion is slight in abiotic soil. Sulfate reducing bacteria (SRB) grow well in the soil. SRB accelerates uniform corrosion of the steel and causes localized corrosion. A high water content in the soil promote the SRB growth and steel corrosion. The presence of CO2 in the soil favors the SRB growth and steel corrosion. Abstract: In this work, corrosion of an X52 pipeline steel was investigated in a field-collected soil containing sulfate-reducing bacteria (SRB) by weight-loss testing, bio-testing, electrochemical measurements and surface analysis techniques. The SRB can grow well in the soil and attach to the steel surface, leading to microbiologically influenced corrosion (MIC) of the steel. The SRB are able to accelerate corrosion of the steel remarkably. Compared to the corrosion rate of 0.0473 mm/y in SRB-absent soil, the corrosion rate of the steel is up to 0.282 mm/y when SRB are contained in the soil. An increase of the water content in the soil favors the growth of SRB, increasing the thickness of the biofilm formed on the steel surface and accelerating the steel MIC. At individual water contents, the presence of CO2 in the soil accelerates the steel MIC induced by SRB, which is associated with the increasing amount of SRB cells in CO2 -containing soil. The SRB also result in localized corrosion of the steel. This is associated with the unique soil corrosion environment, where the sessile SRB cells and corrosion products do not move freely. The porous structure of the surface film contributes to the initiation of localized corrosion.